An Integrative Investigation of Parabistichella variabilis (Protista, Ciliophora, Hypotrichia) Including Its General Morphology, Ultrastructure, Ontogenesis, and Molecular Phylogeny. (15th June 2020) - Dong, Jingyi; Chen, Xumiao; Liu, Yongqiang; Ni, Bing; Fan, Xinpeng; Li, Lifang; Warren, Alan
Abstract: Hypotrichs are a highly differentiated and very diverse group of ciliated protists. Their systematics and taxonomy are challenging and call for detailed investigations on their general morphology, ultrastructure, ontogenesis, and molecular phylogeny. Here, a comprehensive study is conducted on a brackish water population of Parabistichella variabilis using light and electron microscopy and phylogenetic analyses based on small subunit ribosomal DNA sequence data. Its morphology, including the infraciliature, pellicle, nuclei, buccal seal, and extrusomes, is documented. The present findings indicate that in P. variabilis : (i) the cortical granules are extrusomes, which differ from those of other hypotrichs; (ii) the buccal seal is bounded by the plasma membrane and contains a single layer of longitudinal microtubules; (iii) two contractile vacuoles might be present rather than one; and (iv) the pharyngeal disks are bounded by a single membrane. Early‐to‐middle stages of ontogenesis are described for the first time, enabling the complete characterization of this process. Phylogenetic analyses indicate that Parabistichella variabilis is closely related to several species from different genera, such as Orthoamphisiella breviseries, Uroleptoides magnigranulosus, and Tachysoma pellionellum . However, ultrastructural and gene sequence data for more taxa are needed in order to resolve the systematics of Parabistichella .